DIAGNOSIS AND MANAGEMENT OF RECURRENT EXTERNAL OTITIS IN A FELINE: CASE REPORT OF NASOPHARYNGEAL POLYP - COSTA, T. D.; SOUSA, I. S.; RODRIGUES, M. H. (Ars Veterinaria, 2025)
Recurrent external otitis in felines presents a clinical challenge due to its multifactorial nature, complicating differential diagnosis with potential associations to underlying systemic conditions, such as renal disease and the growing threat of antimicrobial resistance. The case study demonstrates the application of a holistic diagnostic approach, incorporating ear cytology, microbiological cultures, antimicrobial susceptibility testing and otoscopy, to identify the underlying etiology and determine the appropriate treatment.